Changes in foraging behaviour suggest competition between wild and domestic ungulates: Guanaco and domestic sheep in southern Patagonia - Lancaster, A.; Corti, P.; Fernandez, T.; Moraga, C. A.; Radic Schilling, Sergio Javier; Hardenberg, A. (My University, 2022)
Previous attempts to address the presence of interspecific competition between domestic livestock and wild ungulates have focused largely on habitat or dietary overlaps. Although overlaps in habitat or diet create opportunities for competition to occur between species, competition only results from such overlap if it affects one or both species negatively. Less attention has been afforded to possible behavioural modifications induced in wildlife by competition with domestic livestock. Here, we investigated the effects of the presence of livestock on feeding behaviour of guanaco (Lama guanicoe) in southern Patagonia, using focal sampling of individuals during foraging bouts, with instantaneous scan samples to estimate group behavioural budgets. We recorded guanaco bite and step rates, used as proxies of foraging intake and selectivity, from four different study sites over eight consecutive seasons. We also estimated sheep and guanaco densities per site, along with vegetation biomass availability. As in other ungulates, bite rates of guanaco appear to be highly flexible and generally increased with vegetation biomass availability. However, as sheep densities and thus additional grazing pressure increased, guanaco foraging strategy compensated by increasing bite rates when foraging vegetation was scarce, indicating further likelihood of competition. Additionally, scan samples indicated that the probability of guanaco feeding occurring at any one time was higher in areas shared with domestic sheep compared to national parks, suggesting guanaco have to focus more on feeding than other behaviours when sheep are present.
Keywords: guanaco; interspecific competition; lama guanicoe; livestock; foraging behaviour; bite rate; dietary overlap; behavioural budgets